Murder and madness on trial : a tale of true crime from early modern Bologna - Calabritto, Monica (Interactions in the early modern age., 2023)
"Explores the 1588 murder trial of Paolo Barbieri in Bologna, examining early modern violence, madness, criminal justice, medical and legal expertise, and the construction and circulation of news"--